Improved Dielectric Constant of Modified Polymer Blend by Nickel Oxide Nanoparticles. (2015) - Khutia, Moumita; Joshi, Girish M.; Pandey, Mayank
Abstract: We fabricated polyvinyl chloride (PVC) and poly (methyl methacrylate) (PMMA) blend and modified by nickel oxide (NiO) nanoparticles. By dispersing 2, 5 and 7 wt% NiO into a [(PVC)m /(PMMA)n )] 60/40 (m/n) wt% polymer blend, three modified blend systems were obtained. The dispersion of NiO in blends was characterized by optical microscopy. The orientation of NiO in PVC/PMMA matrix was confirmed by Atomic Force Microscopy (AFM). The dielectric parameters of pure PVC/PMMA blend and NiO modified PVC/PMMA blend were studied using an impedance analyzer as a function of frequency (10Hz-100 KHz) and DC bias (0-25 V) at room temperature (30°C). The improved dielectric constant was demonstrated in the range of 10 4 to 10 5 . The modified blend can be useful in battery electrode coating application domain.